Synthesis techniques and optimizations for reconfigurable systems - Kastner Ryan; Kaplan Adam; Sarrafzadeh Majid (Boston Kluwer Academic, 2004)
The book provides a framework for reconfigurable system synthesis, which bridges the gap between application-level compiler analysis and high-level device synthesis. The development of this framework (discussed in Chapter 5), and the creation of applicat
Keywords: Computer control; Reconfigurable systems